Analysis of the intellectual structure of knowledge regarding drought vulnerability assessment - Zeinab Asadpourian; Yaser Mohammadi (مجله علم‌سنجی کاسپین)
Background and aim: Given the increasing number of studies on Drought Vulnerability Assessment (DVA), conducting a comprehensive scientometric analysis of scientific results in this field can aid in understanding the current status, trends, and impacts of research. Materials and methods: To create a scientific map of this domain, a total of 1,131 articles from the Scopus database, published from 1990 to 2023, were collected. Scientometric techniques, such as co-authorship networks and co-occurrence networks of keywords, were employed for data analysis. Key indicators, including h-index, citation counts, and journal impact factors, were calculated to assess the visibility and influence of studies. Statistical analyses were performed using R software and VOSviewer. Findings: Results indicated that the growth rate of publications in DVA is approximately 16.5%, with notable increases in both the quality and citation rates of articles over the years. The scientific mapping analysis identified a six-cluster pattern, with the keyword "adaptation and vulnerability management" being the most frequently mentioned. The thematic evolution of studies also showed that in recent years, attention to adaptation issues in drought vulnerability assessment has increased, and a significant relationship was observed between the number of documents and citations (r=0.89) and between the number of authors and citations (r=0.17). Conclusion: Global attention to DVA has significantly risen in recent years, with countries such as the United States, China, and Australia leading the efforts. Furthermore, adaptation management has emerged as the most important research area, while emerging methods and techniques in vulnerability assessment are expected to lead to greater diversity and consensus in this field.